Gambaran Sarana dan Prasarana Bimbingan dan Konseling di Sekolah SMP Swasta Cerdas Murni - Daulay, Nurussakinah; Rambe, Afghan Bai Asy Ary; Hidayat, Dodi; Abdillah, Fahmil; Dewi, Nabila Atari Syafira; Aritonang, Padila Sari (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to describe the facilities and infrastructure of guidance and counseling at the Private Junior High School Cerdas Murni in Deli Serdang Regency, North Sumatra using a qualitative method. The research subjects are the Private Junior High School Cerdas Murni. The data collection instruments are observations and interviews regarding the condition of the guidance and counseling facilities and infrastructure at the Private Junior High School Cerdas Murni. The data analysis technique used is descriptive data analysis. The results of the study show that the availability of counseling rooms is quite adequate, including the availability of special counseling rooms and factors that hinder the availability of guidance and counseling facilities and infrastructure.